(untitled) (International Journal of Innovative Technologies in Economy, 2024)
As the development process intensifies in various regions, countries are increasingly cooperating, leading to greater economic interdependence and integration. Europe and Asia, the largest geo-economic region in the world, cover the biggest landmass and are home to 5 billion people, accounting for 72.5% of the world’s population (12.5% in Europe and 60% in Asia). Eurasia accounts for 60% of the world’s Gross Domestic Product (GDP) and holds three-quarters of the world’s discovered energy resources. The region is home to six highly developed economies and hosts most of the world’s major players in natural resources, manufacturing, and services. There are over 320 socio-economic alliances in this region, one of which is the Eurasian Economic Union (EAEU). In 2015, the Government of Mongolia and the EAEU signed a Memorandum of Cooperation. In 2015, a joint working group was established by the parties, and its first session was held in Ulaanbaatar. The second session took place in Moscow in 2016. In 2020, Mongolia and the EAEU organized the first consultative meeting to establish a joint research team that would explore the feasibility of concluding a free trade agreement. These efforts demonstrate the need for further research in this area. Therefore, this study aims to investigate some of the fundamental issues regarding the national security of Mongolia and to determine future guidelines and methods within the framework of Mongolia’s cooperation with the EAEC.